2015
DOI: 10.1074/jbc.m114.587055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Dominant Negative Effect of a Glycine Transporter 2 Mutation Associated with Hyperekplexia

Abstract: Background: Hyperekplexia is caused by defective glycinergic neurotransmission. Results: A dominant negative glycine transporter-2 mutant is trapped in a calnexin-bound state and retains wild type GlyT2 in the endoplasmic reticulum. Conclusion: Chemical chaperones rescue the folding defect of the mutant and overcome its dominant negative effect. Significance: This opens the way to revert the dominant negative effect exerted by the mutant associated with hyperekplexia in neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…One of them, S510R, affects GlyT2 intracellular trafficking and blocks the arrival of the transporter to the plasma membrane [54]. A detailed study of the pathogenic mechanisms in mutant S512R of the rat sequence (equivalent to the human mutation S510R) indicates that the presence of an arginine residue rather than serine provokes GlyT2 misfolding, enhances its association to the ER-chaperone calnexin, alters the association with the COPII component Sec 24D and, as a consequence, impedes the exit of the transporter from the ER [57]. The S512R mutant forms oligomers with wild-type GlyT2 causing its retention in the ER and therefore the dominant negative effect.…”
Section: Movement Diseases: Hyperekplexiamentioning
confidence: 99%
“…One of them, S510R, affects GlyT2 intracellular trafficking and blocks the arrival of the transporter to the plasma membrane [54]. A detailed study of the pathogenic mechanisms in mutant S512R of the rat sequence (equivalent to the human mutation S510R) indicates that the presence of an arginine residue rather than serine provokes GlyT2 misfolding, enhances its association to the ER-chaperone calnexin, alters the association with the COPII component Sec 24D and, as a consequence, impedes the exit of the transporter from the ER [57]. The S512R mutant forms oligomers with wild-type GlyT2 causing its retention in the ER and therefore the dominant negative effect.…”
Section: Movement Diseases: Hyperekplexiamentioning
confidence: 99%
“…were prepared as described previously 12 . Briefly, the cortex of Wistar rat fetuses was obtained on the 18th day of gestation, and the tissue was mechanically disaggregated in Hanks' balanced salt solution (Invitrogen) containing 0.25% trypsin (Invitrogen) and 4 mg/ml DNase (Sigma).…”
Section: Primary Cultures Of Cerebral Cortex and Transfection-primarymentioning
confidence: 99%
“…Understanding the molecular regulation of GlyT2 transport would provide insight into the molecular and cellular basis of glycinergic neurotransmission and potentially lead to identifying new therapeutic targets for presynaptic Hyperekplexia. Previous studies on GlyT2 regulatory mechanisms revealed that GlyT2 activity is regulated by PKC activation 10,11 , calnexin function 12,13 , P2Y and P2X purinergic receptors 14,15 and interaction with syntaxin1 16 , Na+/K+-ATPase 17 and PMCAs 18 . In addition, we previously described that GlyT2 trafficking and surface expression are regulated by ubiquitination 11,19 , a process in which the small protein ubiquitin is covalently attached to a cytoplasmic lysine residue of a target protein.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, this dysfunction is the main presynaptic cause of Hyperekplexia [7][8][9][10] , but it also may be involved in the pathology of chronic pain 11 and deficits in auditory processing 12 . A better understanding of the molecular regulation of GlyT2 would help framing future studies on the importance of this transporter in human disease and we and others have identified some molecular mechanisms controlling GlyT2 expression and activity [13][14][15][16][17][18][19][20][21][22][23] . Ubiquitination, a post-translational modification in which the small protein ubiquitin is covalently attached to a cytoplasmic lysine residue of a protein, is a major control point that finely tunes the expression of GlyT2 14,17,24,25 .…”
Section: Introductionmentioning
confidence: 99%